2018
DOI: 10.1002/cam4.1807
|View full text |Cite
|
Sign up to set email alerts
|

CTHRC1 overexpression predicts poor survival and enhances epithelial‐mesenchymal transition in colorectal cancer

Abstract: Collagen triple helix repeat containing (CTHRC1), which was identified as a cancer‐related factor, is a promigratory protein involved in multiple processes, including vascular remodeling, antifibrosis, metabolism, bone formation, and cancer. In this study, we aimed to investigate the clinical significance and possible role of CTHRC1 in the process of epithelial‐mesenchymal transition (EMT) in colorectal cancer (CRC). Here, we revealed that CTHRC1 mRNA and protein levels are both upregulated in CRC tissues comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 34 publications
6
36
0
Order By: Relevance
“…CTHRC1 has been reported to be an oncogene in previous studies (21)(22)(23)(24)(25)(26)(27), and it can promote tumorigenesis by multiple mechanisms. It has been confirmed that CTHRC1 can activate the SRC and ERK signal cascades and upregulate the expression of MMP9, thus promoting the invasion of CRC cells (22).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…CTHRC1 has been reported to be an oncogene in previous studies (21)(22)(23)(24)(25)(26)(27), and it can promote tumorigenesis by multiple mechanisms. It has been confirmed that CTHRC1 can activate the SRC and ERK signal cascades and upregulate the expression of MMP9, thus promoting the invasion of CRC cells (22).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, there is a close relationship between CTHRC1 and EMT. Ni et al (21) demonstrated that CTHRC1 can promote epithelial cell metastasis by inducing the EMT in CRC cells. In a study by Kim et al (22), CTHRC1-knockdown prevented EMT and inhibited the proliferation of renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CTHRC1 encodes a protein that may play a role in the cellular response to arterial injury through involvement in vascular remodeling [19]. Previous studies had shown that CTHRC1 promoted tumor cell progression and might play a key role in the invasion and metastasis of cervical carcinoma, cervical squamous cell carcinoma and colorectal cancer [20][21][22]. In addition, CTHRC1 promotes M2-like macrophage recruitment and myometrial invasion in endometrial carcinoma by integrin-Akt signaling pathway [23], which indicated that CTHRC1 might be a biomarker for tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 99%